2008
DOI: 10.1111/j.1572-0241.2007.01756.x
|View full text |Cite
|
Sign up to set email alerts
|

Relapses of Inflammatory Bowel Disease During Pregnancy: In-Hospital Management and Birth Outcomes

Abstract: Treatment with IV hydrocortisone and IV cyclosporine appears effective at inducing remission of colitis but their use must continue to be confined to severely ill patients being treated at specialized centers. Severe relapses of colitis during pregnancy increase the risk of preterm birth and low birth weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(101 citation statements)
references
References 19 publications
2
95
0
4
Order By: Relevance
“…The onset of IBD in a pregnant woman is uncommon and is usually associated with a poor prognosis [1,10] because of an increased overall risk of an adverse neonatal outcome; the most frequently described are preterm delivery and low birth weight [5,[11][12][13] . An accurate patient history is crucial, as are clinical and pertinent investigations to assess colitis activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The onset of IBD in a pregnant woman is uncommon and is usually associated with a poor prognosis [1,10] because of an increased overall risk of an adverse neonatal outcome; the most frequently described are preterm delivery and low birth weight [5,[11][12][13] . An accurate patient history is crucial, as are clinical and pertinent investigations to assess colitis activity.…”
Section: Discussionmentioning
confidence: 99%
“…A first disease attack of UC during pregnancy is uncommon, and is usually associated with an adverse outcome [1] . Antenatal disease progression correlates with activity at the onset of pregnancy: if UC is in remission at the time of conception, it will remain quiescent throughout pregnancy, while if it is active, it will progressively worsen, leading to an increased incidence of stillbirth, preterm delivery, or postpartum complications for both mother and neonate [2][3][4][5][6] . The management of UC during pregnancy is quite different from that in nonpregnant women because medical therapy, radiology, endoscopy, and surgery imply potential risks for the fetus [2,7] .…”
Section: Introductionmentioning
confidence: 99%
“…Moser et al [57] demonstrated ileal disease was a particularly reliable index predicting LBW. Relapse of UC in pregnant women was also associated with LBW and preterm births [58] . Fortunately, increased risks for congenital abnormalities have not been demonstrated in neonates whose mothers had IBD compared to the general population [57] .…”
Section: Pregnancymentioning
confidence: 99%
“…Earlier studies showed active disease at conception was associated with a higher rate of fetal loss [52] and preterm birth [9,28]. Disease activity during pregnancy has also previously been associated with preterm birth and low birthweight [37,46,53,54]. Secondary analysis conducted by Stephansson et al attempted to correlate pregnancy outcomes with disease activity, specifically looking at women who had ever been hospitalized for UC compared with those with outpatient management only [40].…”
Section: Effect Of Ibd On Pregnancy Course and Pregnancy Outcomesmentioning
confidence: 99%
“…Cyclosporine can be used successfully in pregnancy, although it can cause premature labor and small-for-gestational-age (SGA) infants. In general, studies suggest that use of currently available medications to treat flares during pregnancy will lead to successful remission in greater than 80% of cases [37].…”
Section: Management Of Ibd Flares During Pregnancymentioning
confidence: 99%